Age-stratified association between serum uric acid and lumbar bone mineral density in elderly Chinese women with vertebral compression fractures: a cross-sectional analysis - Zhu, Jianxiang; Xia, Zengbing; Min, Jikang; Hu, Wenlin; Li, Heng; Mei, Chao (Frontiers in Medicine, 2025)
ObjectiveTo investigate the association between serum uric acid (SUA) levels and lumbar bone mineral density (BMD) in elderly Chinese women with vertebral compression fractures (VCFs), with a specific focus on age-dependent variations in this association.MethodsWe conducted a cross-sectional study of 490 female patients aged ≥60 years with VCFs. SUA levels served as the primary exposure variable, and lumbar spine BMD was the outcome variable. Multivariate linear regression models were employed to adjust for potential confounders, incorporating comprehensive subgroup analyses.ResultsA statistically significant positive and independent correlation emerged between SUA levels and spine lumbar BMD after multivariable adjustment (β = 0.045, 95% CI 0.026–0.064). The association demonstrated pronounced variability across age groups, with a more robust correlation in patients younger than 75 years (β = 0.069, 95% CI 0.039–0.098) compared to those 75 years and older (β = 0.026, 95% CI 0.002–0.050), revealing a statistically significant interaction (p = 0.008).ConclusionOur findings reveal a nuanced, age-dependent positive correlation between SUA levels and lumbar BMD in elderly Chinese women with vertebral compression fractures. These results suggest SUA may serve as a potential biomarker for fracture risk assessment and bone health evaluation, particularly in younger elderly populations.